The Effect of Scout Extracurricular Activities on The Character of Fifth Grade Students at Madrasah Ibtidaiyah Sabilul Muhtadin Teluk Sebong Bintan - Ediyansyah; Mutmain Natul Mabrurah (Indra institute Research & Publication, 2025)
This study was conducted to determine the effect of extracurricular scout activities on the character of students at MI Sabilul Muhtadin Teluk Sebong and to find out how much influence extracurricular scout activities have on the character of students. This research uses quantitative research methods. Data collection was carried out using a questionnaire method with the research population, namely students from class V MI Sabilul Muhtadin with a sample size of 30 students. Instrument analysis includes validity and reliability analysis. The results of the validity analysis show that all questionnaire statements are valid. Then the results of the reliability analysis show a reliability coefficient of 0.786 for the character of students (Y). The results of this study indicate that extracurricular scouting has an effect on the character of students at MI Sabilul Muhtadin Teluk Sebong. These results are obtained from the analysis of simple regression formulations, namely the level based on the results of Fcount=17.303 with a significance level of 0.000 <0.05, in other words there is an influence between the extracurricular scout variable (X) on the student character variable (Y). Then it can also be seen based on the t value: it is known that tcount is 4.160> ttable 2.048, so it can be concluded that the scout extracurricular variable (X) has an effect on the student character variable (Y). While the results of the overall influence of extracurricular scout activities on the character of students at MI Sabilul Muhtadin are only 38.2%, which is taken from the results of the coefficient of determination analysis.